Analysis of structural performance of existing rc building designated as tsunami evacuation shelter in case of earthquake-tsunami scenarios in lima city - Palacios, Julian (2019)
In 1746, Lima Region was hit by a severe earthquake and a consecutive tsunami in Callao City caused 96% of casualties in the Callao City population. Under SATREPS Project [1], several studies were realized, and they concluded that a severe earthquake (Mw8.6~8.9) may occur in Lima City [2], following by tsunami which may hit a large coastal area. In that sense, harmful scenarios can occur. Based on last studies, and historical earthquake consequences in Callao City; Local government in La Punta, the most tsunami prone district in Callao, has designated 19 reinforced concrete (RC) buildings as tsunami shelters. Nevertheless, the lack of the structural vulnerability studies of these buildings in front of an earthquake and consecutive tsunami scenario, makes uncertain the good performance of the buildings. Guidelines of other countries such as Japan, The United States and Chile, are oriented to calculate the tsunami forces; nevertheless, these guidelines lack information about structural performance of buildings in front of earthquake-tsunami scenarios. This paper describes a methodology to assess the sequential action of the earthquake and the consecutive tsunami to evaluate the structural performance and the damage level to ensure the safety of buildings and their inhabitants.